Influence of temperature variations on growth, injury survival and inactivation of Listeria monocytogenes in goat milk samples at laboratory scale. (7th June 2014) - Migeemanathan, Suguna; Bhat, Rajeev; Wan‐Abdullah, Wan‐Nadiah; Chye, Fook Yee
<x xml:space="preserve">Abstract</x> Transmission of the thermo‐tolerant pathogen Listeria monocytogenes via contaminated milk and its products, can lead to serious food‐borne illness. In this study, the effects of selected temperatures on survival, percentage injury and inactivation of L. monocytogenes in goat milk samples collected from two different farms were evaluated. Low temperature ranges (0, 5, 10 °C) had a bacteriostatic effect; while at temperatures of 25 and 45 °C, this pathogen grew luxuriantly. However, growth was comparatively slow at 15 °C throughout a 12‐h stress period. Furthermore, a high temperature range (50, 55, 60 and 65 °C) resulted in the elimination of this pathogen within 4 h of stress. Results of Scanning Electron Microscopy showed morphological changes in the cells upon induction of stress temperatures.